2011
DOI: 10.1007/s10529-011-0643-3
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized enzymes affect biofilm formation

Abstract: The effect of the activity of immobilized enzymes on the initial attachment of pathogenic bacteria commonly associated with nosocomial infections (Pseudomonas aeruginosa and Staphylococcus epidermidis) was investigated. The proteolytic enzymes, subtilisin A and the glycoside hydrolase cellulose, were covalently attached onto poly(ethylene-alt-maleic) anhydride copolymer films. A comparison between active and heatinactivated surfaces showed that while the activity of immobilized cellulase reduced the attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 21 publications
(30 reference statements)
2
12
0
Order By: Relevance
“…Nevertheless, the above approaches are usually accompanied with side effects of cytotoxicity or development of drug-resistant strains 15) . In recent years, novel coatings strategies based on biofilm-dispersing enzymes have emerged 16) . It is expected that degradation of components in biofilm extracellular polymeric substances (EPS) could inhibit bacteria adhesion and biofilm formation, and also promote detachment of established three-dimensional biofilm 17) .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the above approaches are usually accompanied with side effects of cytotoxicity or development of drug-resistant strains 15) . In recent years, novel coatings strategies based on biofilm-dispersing enzymes have emerged 16) . It is expected that degradation of components in biofilm extracellular polymeric substances (EPS) could inhibit bacteria adhesion and biofilm formation, and also promote detachment of established three-dimensional biofilm 17) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that enzymes such as proteases and amylases could be used for the remediation of biofilms, since biofouling can be drastically decreased in the presence of these enzymes [17]. In a quest to create anti-biofouling coatings and surfaces, Cordeiro et al [18] showed that immobilized enzymes are able to counteract biofouling, and subsequently concluded that co-immobilization of different enzymes is the most effective route to inherently anti-biofouling surfaces. Therefore, a definite need exists for the capability to immobilize different enzymes onto the same matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since biofilm matrix-degrading enzymes do not kill bacteria or inhibit their growth, the chances that resistance to these agents will evolve are reduced [20]. Finally, some enzymes are currently available at affordable prices and are therefore viable for industrial use, and since they are biodegradable and have a low toxicity, they might be attractive as environmentally friendly antibiofilm agents [8]. Starting from the assumption that polysaccharides and proteins are the major fractions of the matrix [13], hydrolytic enzymes such as glycosidases and proteases have been envisaged as interesting biofilm matrix-degrading agents [22].…”
Section: Introductionmentioning
confidence: 99%